The efficacy of BCG TICE and BCG Connaught in a cohort of 2,099 patients with T1G3 non-muscle-invasive bladder cancer - Witjes, J Alfred; Dalbagni, Guido; Karnes, Robert J; Shariat, Shahrokh; Joniau, Steven; Palou, Joan; Serretta, Vincenzo; Larré, Stéphane; di Stasi, Savino; Colombo, Renzo; Babjuk, Marek; Malmström, Per-Uno; et al. (Urologic oncology, 2016)
BACKGROUND: Potential differences in efficacy of different bacillus Calmette-Guérin (BCG) strains are of importance for daily practice, especially in the era of BCG shortage. OBJECTIVE: To retrospectively compare the outcome with BCG Connaught and BCG TICE in a large study cohort of pT1 high-grade non-muscle-invasive bladder cancer patients. DESIGN, SETTING, AND PARTICIPANTS: Individual patient data were collected for 2,451 patients with primary T1G3 tumors from 23 centers who were treated with BCG for the first time between 1990 and 2011. OUTCOME MEASUREMENTS AND STATISTICAL ANALYSIS: Using Cox multivariable regression and adjusting for the most important prognostic factors in this nonrandomized comparison, BCG Connaught and TICE were compared for time to recurrence, progression, and the duration of cancer specific survival and overall survival. RESULTS AND LIMITATIONS: Information on the BCG strain was available for 2,099 patients: 957 on Connaught and 1,142 on TICE. Overall, 765 (36%) patients received some form of maintenance BCG, 560 (59%) on Connaught and 205 (18%) on TICE. Without maintenance, Connaught was more effective than TICE only for the time to first recurrence (hazard ratio [HR] = 1.48; 95% CI: 1.20-1.82; P<0.001). With maintenance, TICE was more effective than Connaught for the time to first recurrence (HR = 0.66; 95% CI: 0.47-0.93; P = 0.019) with a trend for cancer specific survival (HR = 0.36; 95% CI: 0.14-0.92; P = 0.033). For time to progression and overall survival, Connaught and TICE had a similar efficacy. Compared to no maintenance therapy, maintenance BCG significantly reduced the risk of recurrence, progression and death, both overall, and disease specific, for TICE, but not for Connaught. CONCLUSIONS: We found that BCG Connaught results in a lower recurrence rate as compared with BCG TICE when no maintenance is used. However, the opposite is true when maintenance is given. PATIENT SUMMARY: As there is currently a BCG shortage, information on the efficacy of different BCG strains is important. In this nonrandomized retrospective comparison in over 2,000 patients, we found that BCG Connaught reduces the recurrence rate compared to BCG TICE when no maintenance is used, but the opposite is true when maintenance is given.
Keywords: recidiva; T1G3; proporcionální rizikové modely; Humans; Administration, Intravesical; lidé středního věku; Adjuvants, Immunologic; Proportional Hazards Models; aplikace intravezikální; karcinom z přechodných buněk; Drug Evaluation; adjuvancia imunologická; Female; Aged; udržovací chemoterapie; Neoplasm Invasiveness; výsledek terapie; senioři; lidé; Immunotherapy; Maintenance Chemotherapy; BCG vaccine; high grade; Intravesical drug administration; Neoplasm Grading; staging nádorů; Follow-Up Studies; ženské pohlaví; Kaplanův-Meierův odhad; Male; nádory močového měchýře; Middle Aged; Retrospective Studies; recurrence; Treatment Outcome; Carcinoma, Transitional Cell; stupeň nádoru; hodnocení léčiv; progression; Aged, 80 and over; Immunotherapy, Active; BCG Vaccine; Recurrence; BCG Connaught; senioři nad 80 let; invazivní růst nádoru; retrospektivní studie; Kaplan-Meier Estimate; aktivní imunoterapie; Neoplasm Staging; BCG vakcína; mužské pohlaví; bladder cancer; Urinary Bladder Neoplasms; následné studie; BCG Tice